The Effect of Ferrous Sulphate on the Gross and Histological Changes in the Body of Gastric Mucosa of Adult Albino Rats - Shahnila Nadir ,Nida Qasim,Ansa Rabia (Journal of Rawalpindi Medical College, 2015)
Background:To observe the effects of Ferrous sulphate on the body of gastric mucosa of adult albino rats. Methods: An experimental study was carried out on 30 adult albino Wistar rats for 12 weeks.Two groups were made; A and B. They were divided further into A1, A2, B1 and B2 for qualitative parameters and statistical purposes.Group A was kept as control and divided into 2 sub groups; A1 and A2 and was given normal food and water. The experimental group B was divided into 2 sub groups B1 and B2. Ferrous sulphate was given orally for 4 and 12 weeks respectively through gavage needle for maximum efficacy in the experimental group.Albino rat’s stomach was dissected, fixed in 10% formalin and processed for light microscopy. The short and long term effects of ferrous sulphate were observed on 4th and 12th week respectively. For histological analysis H&E was used. Body of gastric mucosa of adult albino rat was considered for this study. Results: Change in the colour of mucosa was found in 10 (100%) of cases at 12 weeks whereas only 8 (80%) cases showed changes after 4 weeks. Haemorrhage was seen scattered in 4 (40%) cases after 4 weeks whereas present in all 10 (100%) cases after 12 weeks. Ulcer was seen in 4 (40%) of cases after 12 weeks. Epithelial changes were seen in 5 (50%) cases at 4 and 8 (80%) of cases after 4 and 12 weeks respectively. Ulcerative changes were seen in 4 (40%), granulation tissue/ fibrosis was seen in 7 (70%) cases in experimental group only. There was a significant decrease in the weight of rats from 226.69 ±22.31mg to 169.43±22.39mg in the experimental group with p ˂.001. Inflammatory cell count significantly increased from (4.03± 1.02) to 17.01±5.01 in the experimental group with p˂.001. Conclusion: Ferrous Sulphate has detrimental effects on the gastric mucosa of adult albino rats. Haemorrhages, ulcerated areas and change in colour of mucosa was observed with naked eye. Inflammatory cell infiltrate was found to be the most common presentation.